Trends and Challenges in Infrastructure Investment in Low-Income Developing Countries - Gurara, Daniel (IMF Working Papers; Working Paper ;, 2017)
This paper examines trends in infrastructure investment and its financing in low-income developing countries (LIDCs). Following an acceleration of public investment over the last 15 years, the stock of infrastructure assets increased in LIDCs, even though large gaps remain compared to emerging markets. Infrastructure in LIDCs is largely provided by the public sector; private participation is mostly channeled through Public-Private Partnerships. Grants and concessional loans are an essential source of infrastructure funding in LIDCs, while the complementary role of bank lending is still limited to a few countries. Bridging infrastructure gaps would require a broad set of actions to improve the efficiency of public spending, mobilize domestic resources and support from development partners, and crowd in the private sector.